(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The objective of the present study is to highlight college library budgets in Kachchh region. In includes expenditure of library budgets and their source of finance. The present study has various aspects. One of them is the assessment of the present budgetary status of private college libraries in Kachchh region and to find out need of change, to suggest practical solutions to the prevailing problems of the college libraries with the help of the questionnaire method, the questionnaire was sent to all 10 Arts, Commerce and Science colleges.